Towards Abel Prize: The Generalized Brownian Motion Manifold's Fisher Information Matrix with Info-Geometric Applications to Energy Works - Mageed I.A.; Zhang Q.; Akinci T.C.; Yilmaz M.; Sidhu M.S. (Institute of Electrical and Electronics Engineers Inc., 2023)
Fisher information matrix; Geometry; 'current; Energy; Energy work; Fisher information matrices; Fisher information matrix; Generalized brownian motion; Information geometry; Statistical manifold; Statistical manifolds; Brownian movement